2018
DOI: 10.1002/jbio.201800185
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo phasor analysis of stoichiometry and pharmacokinetics using short‐lifetime near‐infrared dyes and time‐gated imaging

Abstract: We introduce a simple new approach for time‐resolved multiplexed analysis of complex systems using near‐infrared (NIR) dyes, applicable to in vitro and in vivo studies. We show that fast and precise in vitro quantification of NIR fluorophores' short (subnanosecond) lifetime and stoichiometry can be done using phasor analysis, a computationally efficient and user‐friendly representation of complex fluorescence intensity decays obtained with pulsed laser excitation and time‐gated camera imaging. We apply this ap… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
89
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

6
3

Authors

Journals

citations
Cited by 46 publications
(93 citation statements)
references
References 70 publications
4
89
0
Order By: Relevance
“…In this study, the goal was to test TZM–HER2 binding via FLIM-FRET imaging in vitro. In AU565 cells, donor TZM–AF700, in the absence of acceptor TZM–AF750, shows average lifetime values (≈1–1.1 ns), as shown previously for other NIR FRET probes [ 19 , 36 ], whereas in the presence of an acceptor, a significantly reduced lifetime is detected, indicating the occurrence of FRET due to TZM–HER2 interactions. Of importance, in AU565 cells, we found the shortest lifetime species at the plasma membrane, which may be due to the extensive HER2 clustering at the cell surface [ 37 , 38 , 39 ].…”
Section: Discussionsupporting
confidence: 84%
“…In this study, the goal was to test TZM–HER2 binding via FLIM-FRET imaging in vitro. In AU565 cells, donor TZM–AF700, in the absence of acceptor TZM–AF750, shows average lifetime values (≈1–1.1 ns), as shown previously for other NIR FRET probes [ 19 , 36 ], whereas in the presence of an acceptor, a significantly reduced lifetime is detected, indicating the occurrence of FRET due to TZM–HER2 interactions. Of importance, in AU565 cells, we found the shortest lifetime species at the plasma membrane, which may be due to the extensive HER2 clustering at the cell surface [ 37 , 38 , 39 ].…”
Section: Discussionsupporting
confidence: 84%
“…A separate Cy3B sample was used as the reference dye for phasor calibration, using a τ = 2.5 ns (value measured by TCSPC). µ is the initial dye concentration ratio and χ is the product of the extinction coefficient ratio and quantum yield ratio for both dyes (23). 10 µL of a stock solution of this QD sample (concentration ~ 1 µM) was left to dry on a coverslip and imaged in ambient conditions using the same setup as used in the previous measurements.…”
Section: Phase Lifetime Map For Complex Samplesmentioning
confidence: 99%
“…In contrast, as expected, the urinary bladder showed very low levels of FD%, suggesting that fluorescence signal is due to excreted Tf-AF700 degradation products. [22][23][24] Although successful, this study was performed using a sequential imaging protocol that increases workload, can lead to some registration errors 8 between the spatial mapping of the biomarkers, and may introduce biological bias due to the dynamic nature of tumor biology. Therefore, we investigated the potential of using dark quencher QC-1 as an alternative FRET acceptor to enable multiplexed imaging in the same animal and concurrent imaging session (Suppl.…”
Section: Monitoring Target Engagement and Metabolic Levels In Tumor Xmentioning
confidence: 99%
“…18,21 Recently, our group has pioneered Near-Infrared (NIR) Macroscopic FLI-FRET (MFLI-FRET) to quantitatively monitor ligand-target engagement, a critical component of targeted drug delivery, in live and intact animals. [22][23][24] Using 4 the transferrin (Tf)-transferrin receptor (TfR) system as a biological model, we demonstrated that MFLI-FRET quantitatively reported on intracellular delivery of the drug carrier ligand, providing a non-invasive direct readout of the true payload delivered to pathological cells in live intact animals. 22 Hence, MFLI-FRET is poised to become a mainstream analytical tool to assess target engagement of the ligand-or antibody to their respective receptors in preclinical studies.…”
Section: Introductionmentioning
confidence: 99%